Background of Parents Including Their Children Practicing Martial Arts Sports in Merauke Regency (Department of Physical Education, Sport, Health and Recreation, 2019)
This study aims to determine the background of parents of martial arts participants in Merauke district. The subjects in this study were parents of students, consisting of men and women. The sample involved in this study were 217 parents consisting of four types of martial arts in Merauke Regency. The data collection technique uses a questionnaire. The questionnaire used is a Likert scale with four types of answer choices. Questionnaires were made based on sports goals from the 2005 National Sports System Act. Data analysis methods used descriptive quantitative. The results of this study indicate that the background of parents involving their sons and daughters in martial arts is 32.26% due to sports achievement goals, 28.55% due to recreational sports backgrounds and 39.18% due to educational sports background. Based on the results of this study, it can be concluded that the background of parents includes their children practicing martial arts in Merauke Regency due to educational sports goals.